2021
DOI: 10.1002/jsfa.11585
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of low‐cost agricultural by‐product rice husk for Monascus pigments production via submerged batch‐fermentation

Abstract: BACKGROUND: Monascus pigments (MPs) produced by the genus Monascus, have been utilized for more than 2000 years in the food industry. In the present study, by submerged batch-fermentation (SBF), we were able to obtain a mutant strain with a high tolerance of inhibitory compounds generated from rice husk hydrolysate, allowing the production of MPs.RESULTS: The mutant strain, M. Purpureus M523 with high rice husk hydrolysate tolerance was obtained using the atmospheric and room temperature plasma (ARTP) screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…However, studies on functional RMR with high GABA concentrations are limited compared to those on pigment‐rich RMR and monacolin K‐rich RMR. To enhance the GABA production ability of M. purpureus M1, we employed an ARTP breeding system, which has also been used to improve the monascus pigment production ability of M. purpureus in our previous study 16–18 …”
Section: Resultsmentioning
confidence: 99%
“…However, studies on functional RMR with high GABA concentrations are limited compared to those on pigment‐rich RMR and monacolin K‐rich RMR. To enhance the GABA production ability of M. purpureus M1, we employed an ARTP breeding system, which has also been used to improve the monascus pigment production ability of M. purpureus in our previous study 16–18 …”
Section: Resultsmentioning
confidence: 99%
“…Immobilized fermentation was performed according to the method in our previous study, with several modifications ( Liu et al, 2019b ; Zhang et al, 2022 ). The spores of mutant strain M. purpureus H14 were immobilized in different ratios of sodium alginate (SA) and polyvinyl alcohol (PVA) solution [3% (wt/wt):0% (wt/wt), 2.5% (wt/wt):0.5% (wt/wt), 2% (wt/wt):1% (wt/wt), and 1.5% (wt/wt):1.5% (wt/wt)] instead of in 3% (wt/wt) sodium alginate solution.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, mutant strains including M. purpureus M183 with high MP production, M. purpureus M630 with high exMP production, and M. purpureus M523 with high rice husk hydrolysate tolerance were generated using the ARTP screening system ( Liu et al, 2019b , 2020b ). In addition, heavy ion beam irradiation (HIBI), a novel and more efficient irradiation method for strain mutagenesis, has unique physical and biological advantages due to its high linear energy transfer and relative biological effectiveness, wide mutation spectrum, and high mutation rate ( Gao et al, 2020 ; Guo et al, 2020 ; Zhang et al, 2022 ). Previous studies have demonstrated that HIBI produces a high mutation rate, mainly attributed to deletions, nucleotide exchange, and insertions ( Chen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another approach, a mutant strain of M. purpureus M523 was generated by the use of atmospheric and room temperature plasma (ARTP) screening system, which exhibited high tolerance to non-detoxified acid hydrolyzate of rice husk. The employment of this mutant strain spores immobilized in sodium alginate, enabled pigment production of 80.7 U/mL from rice husk ( Zhang S. et al, 2021 ).…”
Section: Agro-industrial Wastes As Low-cost Substrates For Pigment Pr...mentioning
confidence: 99%